Budgeting and Financial Management in The Federal Government - Jeery L McCaffery, L. R. Jones (IAP, 2001)
The books in this series aim to be provide a forum for sharing ideas, concepts and results of research and practice in the field of public management, and to stimulate critical thinking about alternative approaches to problem solving and decision making in the public sector.